Analisis Tingkat Pemahaman Pelaksanaan Evaluasi pada Guru Penjasorkes di Sekolah Dasar Sekecamatan Klangenan Kabupaten Cirebon - Faujiyah, Faujiyah; Nugraha, Eka; Ma’mun, Amung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to understand the implementation of evaluations for Physical Education teachers in State Elementary Schools in Klangenan District, Cirebon Regency. The research uses a quantitative descriptive method, with a survey research design in the form of a questionnaire. The instrument used is a closed questionnaire instrument using a 4-point Likert scale; the data analysis technique used is descriptive analysis in the form of percentages. The sample in this study was 18 teachers from public elementary school physical education teachers in Klangenan District, Cirebon Regency. This was the use of a total sampling technique, where the entire population approach that was the object of research was included as a sample. Based on the results and analysis in this research, several conclusions can be drawn that the average understanding of the implementation of physical education teacher evaluations in State Elementary Schools in Klangenan District, Cirebon Regency, is at a value of 125.39, which indicates the overall category is 'Sufficient.' However, further descriptive statistical analysis revealed that 11 teachers, covering approximately 60% of the respondents, demonstrated a level of understanding that fell into the 'Poor' category. In conclusion, the results of this research may indicate that there are areas where the interpretation and application of evaluation among Physical Education teachers still require special attention to be improved. Keywords: Implementation of Evaluation, Physical Education